Lysosomal TFEB‐TRPML1 Axis in Astrocytes Modulates Depressive‐like Behaviors - Mo, Jia‐Wen; Kong, Peng‐Li; Ding, Li; Fan, Jun; Ren, Jing; Lu, Cheng‐Lin; Guo, Fang; Chen, Liang‐Yu; Mo, Ran; Zhong, Qiu‐Ling; Wen, You‐Lu; Gu, Ting‐Ting; et al. (Advanced science, 2024)
Lysosomes are important cellular structures for human health as centers for recycling, signaling, metabolism and stress adaptation. However, the potential role of lysosomes in stress‐related emotions has long been overlooked. Here, it is found that lysosomal morphology in astrocytes is altered in the medial prefrontal cortex (mPFC) of susceptible mice after chronic social defeat stress. A screen of lysosome‐related genes revealed that the expression of the mucolipin 1 gene (Mcoln1; protein: mucolipin TRP channel 1) is decreased in susceptible mice and depressed patients. Astrocyte‐specific knockout of mucolipin TRP channel 1 (TRPML1) induced depressive‐like behaviors by inhibiting lysosomal exocytosis‐mediated adenosine 5′‐triphosphate (ATP) release. Furthermore, this stress response of astrocytic lysosomes is mediated by the transcription factor EB (TFEB), and overexpression of TRPML1 rescued depressive‐like behaviors induced by astrocyte‐specific knockout of TFEB. Collectively, these findings reveal a lysosomal stress‐sensing signaling pathway contributing to the development of depression and identify the lysosome as a potential target organelle for antidepressants. This study indicates that chronic stress alters the morphology of astrocytic lysosomes and the mucolipin TRP channel 1 (TRPML1) expression in the mPFC of susceptible mice. Astrocyte‐specific knockout of TRPML1 results in depressive‐like behaviors in mice by inhibiting lysosomal exocytosis‐mediated adenosine 5'‐triphosphate (ATP) release. This stress response of astrocytic lysosomes is mediated by the transcription factor EB (TFEB).